Single‐cell transcriptomics analysis of mild cognitive impairment in World Trade Center disaster responders. Issue 1 (20th February 2021) - Kuan, Pei‐Fen; Clouston, Sean; Yang, Xiaohua; Che, Chang; Gandy, Samuel; Kotov, Roman; Bromet, Evelyn; Luft, Benjamin J.
Abstract: Introduction: Recent research has found that World Trade Center (WTC) responders in their mid‐50s have an elevated prevalence of mild cognitive impairment (MCI) that is associated with neural degeneration and subcortical thinning. This article extends our understanding of the molecular complexity of MCI through gene expression profiling of blood. Methods: The transcriptomics of 40 male WTC responders were profiled across two cohorts (discovery: nine MCI and nine controls; replication: 11 MCI and 11 controls) using CITE‐Seq at single‐cell resolution in blood. Results: Comparing the transcriptomic signatures across seven major cell subpopulations, the largest differences were observed in monocytes in which 226 genes were differentially expressed. Pathway analysis on the genes unique to monocytes identified processes associated with cerebral immune response. Discussion: Our findings suggested monocytes may constitute a key cell type to target in blood‐based biomarker studies for early detection of risk of MCI and development of new interventions.